Emerging Role of Toll-like Receptors in Atherosclerosis - Hadi, Najah R.; Shaker, Saad Rasool; Alharis, Nada R (Important Aspects of Toll-like Receptors: Signaling Pathways in Diseases, 2021)
Atherosclerosis, the leading cause of cardiovascular disease (CVD), is driven by inflammation. Increasing evidence suggests that toll-like receptors (TLRs) are key orchestrators of the atherosclerotic disease process. Interestingly, a distinct picture is being revealed for individual receptors in atherosclerosis. TLRs exhibit a complex nature enabling the detection of multiple motifs named danger-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs). Activation of these receptors triggers an intracellular signalling cascade mediated through MyD88 or TRIF, leading to the production of pro- and anti-inflammatory cytokines. Inflammation drives atherosclerosis. Both immune and resident vascular cell types are involved in the development of atherosclerotic lesions. The phenotype and function of these cells are key in determining the development of lesions. Toll-like receptors are the most characterised innate immune receptors and are responsible for the recognition of exogenous conserved motifs on pathogens, and, potentially, some endogenous molecules. Both endogenous and exogenous TLR agonists may be present in atherosclerotic plaques. Engagement of toll-like receptors on immune and resident vascular cells can affect atherogenesis as signalling downstream of these receptors can elicit proinflammatory cytokine release, lipid uptake, and foam cell formation and activate cells of the adaptive immune system.